Mapping the nutrient adequacy of farm production and food consumption to target policy in Uganda - Marivoet, Wim; Ulimwengu, John M. (Wiley, 2022)
Spatial variation in crop and livestock production, combined with variation in market purchases and food transfers, lead to geographic differences in malnutrition that can inform food system policies.This article quantifies nutrient production and consumption by sub‐region in Uganda, to identify the magnitude and location of gaps left by farm households’ own production, market purchases, and food transfers relative to household nutrient requirements.Using the fourth round of Uganda’s National Panel Survey (2013/2014), we convert households’ food production and consumption to nutrient equivalents, then identify the spatial pattern of nutrient inadequacy relative to requirements in each sub‐region. To inform policy, we identify the main food sources of five key micronutrients as well as their least‐cost alternatives to fill corresponding gaps.Sufficient calories and protein are generally available from farm production, purchases, and transfers, but alarming deficits can be seen in the supply of calcium, iron, and zinc as well as vitamins A and B12. Deficits are especially marked in the North East sub‐region. A variety of foods currently available in small quantities could be scaled up to fill these gaps.We find severe limitations in the available data, however, revealing the need for future work to cover all nutrient sources throughout the year with sufficient spatial and temporal precision to target interventions.The data analysed provide a suggestive but incomplete picture of how farm production, food markets, and transfers could be enhanced to meet nutrient requirements. Candidate foods for production and marketing to fill nutrient gaps include diverse vegetal crops, milk, and fish. Perishability, transport, and high production costs currently limit supply while low incomes limit demand, implying that a variety of food system interventions as well as social protection transfers are needed to fight hidden hunger in Uganda.